Karakteristik Fisik dan Mekanik Edible Film Berbasis Pati Kacang Merah (Phaseoulus vulgaris) dan Gel Okra (Abelmoschus esculentus L) - Nur Aini Dwi Cahyo; Warkoyo Warkoyo; Rista Anggriani (Universitas Muhammadiyah Malang, 2021)
Red bean starch is a food ingredient that has a high starch content, which can be used as an edible film. Edible films from the starch group still have shortcomings, namely having brittle and stiff properties, so it is necessary to add other materials to improve the properties of the edible film , namely by adding okra gel. The addition of okra gel is expected to improve the physical and mechanical properties of the edible film. The purpose of this study was to determine the interaction with the addition of variations in the concentration of red bean starch and okra gel on the physical and mechanical characteristics of the edible film. This research consists of two research factors. The first factor is the concentration of red bean starch which consists of 3 levels, namely 4%; 5%; 6; (b / b). The second factor was the concentration of okra gel which consisted of 3 levels, namely 3%; 8%; 13% (w / v). The experiment used a factorial randomized block design (RBD). Observation parameters include analysis of thickness, transparency, tensile strength, elongation, water vapor transmission rate and solubility. The results of this study indicate that there is no interaction between the addition of red bean starch and okra gel on thickness, transparency, tensile strength, elongation, water vapor transmission rate and solubility edible film. The best treatment with results that were close to standard was edible film with a concentration of 5% (w / w) red bean starch and 3% (w / v) of okra gel concentration. The results of the best treatment were 0.16 mm thickness, 4.87 MPa tensile strength, 18.02% elongation, 4.73 g / m2/ day WVTR, 45.14% solubility and 3.98 A / mm transparency.